Marginal Willingness to Pay for Education and the Determinants of Enrollment in Mexico - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2015)
Standard benefit-incidence analysis assumes that the subsidy, and quality of education services are the same for all income deciles. This strong assumption tends to minimize the distributional inequity at various education levels. Using a new approach, emphasizing marginal willingness to pay for education, the authors analyze the impact of public spending on the education spending behavior of the average household. They address several questions: What would an average household, with a given set of characteristics be willing to spend on an individual child, with given traits if subsidized public education facilities were unavailable? What would the household have saved by sending the child to public school rather than private school? How great are these savings for various income groups? What are the determinants of enrollment by income group, and by location? How do individuals' education expenditures affect enrollment patterns? Among their findings: 1) The non-poor households in urban areas get much of the subsidy, or "savings" from government provision of education services. 2) The wealthy value private education more than the poor do. 3) Differences in school quality are greater at the primary level. In other words, wealthy households get the lion's share of benefits from public spending on education. Household school enrollment, and transition to the next level of schooling, depend heavily on the cost of schooling, how far the head of the household went in school, the per capita household income, and the housing facilities, or services. But the government's effort also affects the probability of enrollment, and transition. The probability of enrollment is much higher for the 40 percent of higher-income households in urban areas, than it is for the 40 percent of lower-income households in rural areas. The best way to increase school enrollment is to successfully target public spending on education to poor households.